2020
DOI: 10.15376/biores.16.1.546-557
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and morphological changes in fibre structure due to material heating during ultrasonic-assisted embossing of cardboard

Abstract: Embossing is a commonly used design element on printed products and packaging. It enhances the product impression with optical and haptic effects. The material deformation during the embossing of cardboard is normally done using high mechanical pressure between two dies. The use of ultrasound in the embossing process leads to a noticeable reduction of the embossing pressure and a greater embossing precision. However, there is a noticeable heating of the cardboard during the ultrasonic-assisted embossing proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Fiber lengths of approximately 20 µm were recorded in the fibers fraction. The fiber lengths and the distribution of the fiber lengths differed only slightly in the outer (a) and inner (b) layers of Material B -350 (Käppeler et al 2020). The majority of the fiber length was around 1000 µm.…”
Section: Experimental Materialsmentioning
confidence: 95%
See 1 more Smart Citation
“…Fiber lengths of approximately 20 µm were recorded in the fibers fraction. The fiber lengths and the distribution of the fiber lengths differed only slightly in the outer (a) and inner (b) layers of Material B -350 (Käppeler et al 2020). The majority of the fiber length was around 1000 µm.…”
Section: Experimental Materialsmentioning
confidence: 95%
“…For instance, this originates from the various fiber's geometries. The fiber lengths of Material B -350 have already been investigated in previous studies, such as by Käppeler et al (2020). Fiber lengths of approximately 20 µm were recorded in the fibers fraction.…”
Section: Experimental Materialsmentioning
confidence: 98%
“…5813 The curvature of the spherical cap element would likely result in less dynamic compression occurring compared to the flatter truncated pyramid, resulting in more localized differences in material compression (Hofmann and Hauptmann 2020) from the spherical cap element. The simultaneous heating and drying of the material resulting from the ultrasonic energy in a loosening of the fiber structure (Käppeler et al, 2021) is likely to result in more voids being present in the fiber network and an increase in the out-ofplane recovery. Therefore in the areas of low compaction, such as near the top of the spherical cap embossing, the use of ultrasonic energy could lead to increases in re-swelling.…”
Section: Bioresourcescommentioning
confidence: 99%
“…This could lead to a better forming result with ultrasonic-assisted embossing, because the cardboard properties influence the embossing resistance. A change in the chemical composition and morphological properties of cardboard due to the energy input of ultrasound could not be demonstrated (Käppeler et al 2021). Hofmann and Hauptmann (2020) showed that the influence of ultrasound on the dynamic material compression depends on the specific material properties of the cardboard used.…”
Section: Introductionmentioning
confidence: 97%